Gen Z investment behavior: Does literation in line with intention? - Arniati Arniati (Jurnal Inovasi Ekonomi, 2021)
This study aims to reveal the characteristics of literacy and investment intention of Generation Z (Gen Z). This type of research is descriptive with 80 respondents. The results showed that the investment intention of Gen Z was in a good category but was not accompanied by a sufficient level of literacy. This study provides a preliminary offer that the unique characteristics of Gen Z are very likely to lead to higher intention without proper knowledge.